The relation between oxytocin receptor gene polymorphisms, adult attachment and Instagram sociability: An exploratory analysis. Issue 9 (September 2021) - Carollo, Alessandro; Bonassi, Andrea; Cataldo, Ilaria; Gabrieli, Giulio; Tandiono, Moses; Foo, Jia Nee; Lepri, Bruno; Esposito, Gianluca
Abstract: Oxytocin is a primary neuropeptide which coordinates affiliative behavior. Previous researchers pointed to the association between genetic vulnerability on Oxytocin Receptor Gene ( OXTR ) and environmental factors (e.g., social relationships) to comprehend social behavior. Although an extensive knowledge of in-person social interactions has been obtained, little is known about online sociability. A gene-environment perspective is adopted to examine how OXTR and adult attachment moderate Instagram behavior. The genetic factors within the regions OXTR /rs53576 (A/A homozygotes vs G-carriers) and OXTR /rs2254298 (G/G homozygotes vs A-carriers) were assessed. The Experience in Close Relationships-Revised (ECR-R) questionnaire was used to collect participants' (N = 57, 16 males) attachment with a partner. The number of posts, followed people ("followings") and followers were obtained from Instagram, and the Social Desirability Index (SDI) was calculated as the ratio of followers to followings. Interaction effects between OXTR groups and ECR-R scores on the number of posts and SDI were hypothesized. Results showed an effect of rs53576 on the number of Instagram followings. Specifically, people with A/A OXTR /rs53576 genotype had more followings than G-carriers independent of the anxiety or avoidance felt towards their partner. These preliminary results offer insights into future investigations on social media behavior. Abstract : Gene*Environment; Adult attachment; Close relationship; Oxytocin Receptor Gene; rs53576; rs2254298; Online behavior; Social media; Social network; Instagram